2022
DOI: 10.3389/fpubh.2022.942595
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Evidence to Guide Decision-Making in the Use of Acupuncture for Postpartum Depression

Abstract: BackgroundThere is conflicting evidence on the effectiveness of acupuncture in the treatment of postpartum depression (PPD). This study aimed to assess previous systematic reviews/meta-analyses (SRs/MAs) on the effectiveness of acupuncture to treat PPD.MethodSRs/MAs regarding the use of acupuncture for PPD were identified from the establishment of digital databases to November 2021. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2) was applied to evaluate the methodological quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Acupuncture may mediate complex processes involving interactions between physical and physiological factors [ 62 ]. Acupuncture seems effective in treating postpartum depression [ 63 ], which may be a contributing factor to PH [ 64 ]. However, no study has measured the emotional status of women with PH.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture may mediate complex processes involving interactions between physical and physiological factors [ 62 ]. Acupuncture seems effective in treating postpartum depression [ 63 ], which may be a contributing factor to PH [ 64 ]. However, no study has measured the emotional status of women with PH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses ( 42 , 43 ) have shown the potential benefits of acupuncture, including manual acupuncture, moxibustion and other techniques for PPD ( 44 46 ), but did not specifically discuss the efficacy and safety of EA in PPD treatment. Therefore, this meta-analysis aims to further explore the efficacy and safety of EA in treating PPD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis included six systematic reviews/meta-analyses of acupuncture for PPD to assess its effectiveness. Three of them reported that acupuncture was more effective than controls, and three found no difference, making it difficult to draw consistent conclusions (Hu et al, 2022 ). In summary, the current study confirms that acupuncture has some efficacy in the treatment of PPD, but the mechanism is unclear, and the evidence is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It can play a role in alleviating depressive symptoms by toning down emotions and harmonizing qi and blood (Yan et al, 2021 ). Nevertheless, the mechanisms of action behind the beneficial effects of acupuncture for PPD are controversial, and there is still a lack of strong evidence for its effectiveness and safety (Yang et al, 2018 ; Hu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%